Profile of Medico-legal Cases Coming to Emergency ward of B. P. Koirala Institute of Health Sciences - Yadav, Ajay Kumar; Shah, B.; Budhathoki, S.S.; Chaudhuri, S.; Aryal, B.D.; Malla, G.B. (Journal of BP Koirala Institute of Health Sciences, 2018)
Background: Medico-legal case usually presents as an emergency case in any hospital. Profiling of these cases provides with evidence on the burden of the medico-legal cases and identifying ways to better manage these cases in the emergency ward of hospitals. Objective: To study the profile of medico-legal cases coming to the emergency ward of B. P. Koirala Institute of Health Sciences (BPKIHS), Dharan, Nepal. Material & Methods: We conducted a retrospective review of all medico-legal cases presenting in the emergency ward of BPKIHS from April 2015 to March 2016. The cases were profiled for socio-demography, injury and diagnosis from the medico-legal register at the emergency ward of BPKIHS. Results: Medico-legal cases comprise almost 10% of all cases at the emergency ward of BPKIHS. A total of 3,715 cases were included in this study. Half (50.0%) of the cases fell in to the category of 25-59 years. Males were almost twice (62.7%) in number, compared to females (37.3%). The top three diagnoses among medico-legal cases are road traffic accidents (41.81%), physical assault (21.13%) and poisoning (20.08%). Other diagnoses were burns, fall injury, sexual assault, self inflicted injury, hanging, gunshot injury, stab injury, machinery injury, drug overdose, blast injury, brought dead, trauma by animal, electrical injury, snake bite and human bite. Conclusions: There are significant numbers and wide varieties of medico-legal cases that present in the emergency ward of BPKIHS. Given the large number of cases presenting at BPKIHS, there is a potential for future research on medico-legal cases for academic and policy purpose.